Sources of Racial Wage Inequality in metropolitan labor markets: Racial, Ethnic, and Gender Differences - McCall, Leslie (American Sociological Review, 2001)
Research on racial inequality has become increasingly specialized, often focusing on a single explanation and subgroup of the population. In a diverse society, a broader comparative framework for interpreting the causes of wage inequality for different racial, ethnic, and gender groups is called for. The effects of a range of different factors on the wages of Latinos, Asians, and blacks, relative to whites and separately for women and men, are examined. New sources of racial wage inequality are also considered. Significant differences are found in the sources of wage inequality across race, ethnicity, and gender. Differences are generally greater between racial and ethnic groups than between men and women. Key findings include a large negative effect of immigration on the relative wages of Latinos and Asians and only a small effect on the relative wages of black women (and no effect on black men). In contrast, the relative wages of blacks remain most affected positively by the presence of manufacturing employment and unions. New economy indicators of high-skill services and flexible employment conditions play only a secondary role in explaining metropolitan racial wage inequality.